Influence of carbon-ion irradiation on the superconducting critical properties of MgB2 thin films (vol 32, 025006, 2019) - Jung, Soon-Gil; Son, Seung-Ku; Pham, Duong; Lim, Weon Cheol; Song, Jonghan; Kang, Won Nam; Park, Tuson (Institute of Physics Publishing, 2021)
We have found that there was an error in the calculation of the atomic density of Mg and B in MgB2. The number of MgB2 molecules per cm3 (pMgB2) is around 3.4×1022, so the number of Mg and B atoms per cm3 must be equal to pMgB2 and twice that of pMgB2, respectively. However, the number of Mg and B atoms per cm3 presented in page 7 correspond to 1/3 and 2/3 of pMgB2, respectively. In order to estimate the atomic density, the mass density of bulk value is much more useful than that of strained sample such as a thin film. Since MgB2 has the mass density of 2.57 g cm-3 and the molar mass of 45.93 g mol-1, and Avogadro's number NA ？ 6.02 × 1023 mol-1, the pMgB2 is approximately 3.37 × 1022 molecules cm-3. Therefore, the number of Mg and B atoms per cm3 in MgB2 must be ∼3.37 × 1022 atoms cm-3 and 6.74 × 1022 atoms cm-3, respectively, and the atomic density of MgB2 is around 10.11 × 1022 atoms cm-3. We believe that the change in atomic density does not lead to any significant issues for all the results and conclusions drawn in the paper. ？ 2021 Institute of Physics Publishing. All rights reserved.